Genetic architecture of resistance to yellow vein mosaic virus disease in advance lines of okra (Abelmoschus esculentus) - BHARATHKUMAR, M V; DHANKHAR, S K; DAHIYA, M S; SRIKANTH, M (The Indian Journal of Agricultural Sciences, 2019)
An experiment was under taken in rainy seasons of 2015 and 2016 to estimate the gene action involved in inheritance of resistance to Yellow Vein Mosaic Virus (YVMV) disease in okra (Abelmoschus esculentus (L.) Moench). Thirty okra advance lines were screened against the natural incidence of YVMV disease in northern Indian condition during rainy season of year 2015, which is the most congenial season for population build-up of whiteflies (Bemicia tabaci), the vector of YVMV. Two resistant (HBT-12 & HB-1157) and two susceptible (HBT-49 & HBT-24) lines were identified and crossed in resistant Ã— susceptible fashion to obtain four hybrids and their advanced generations, viz. first and second filial generations (F1 and F2) and backcrosses (BC1 and BC2) to study their segregation pattern for YVMV resistance and to record the days to first appearance of YVMV disease in various generations of the crosses, thereby to reveal the gene action involved in these resistant lines. Qualitative analysis for YVMV resistance through segregation in the F2s and backcrosses of four cross combinations revealed the involvement of two complementary dominant genes in HBT-12 and a single dominant gene in HB-1157, while involvement of additive gene action in all these crosses was revealed by quantitative analysis performed for disease related trait, days to first disease appearance via generation mean analysis.